2010
DOI: 10.1080/13636820903427561
|View full text |Cite
|
Sign up to set email alerts
|

Playing the numbers game: Connexions personal advisers working with learners on entry to employment programmes

Abstract: Transitions of young people from school to employment, further education or training have been a focus of government policy in the UK for at least the last three decades. Since the late 1990s, numerous policy initiatives have been introduced by New Labour in an attempt to reduce social exclusion through the increased participation of young people in work-related training. This paper reports on a mixed-methods research project exploring Entry to Employment (E2E) provision in the north of England. It outlines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Some related to the role of E2E tutor and the work of Connexions PAs, and are discussed in Thompson (2010) and Russell, Simmons and Thompson (2010), respectively. In this paper, three broad themes concerning learners are explored: how they came to access E2E; their learning experiences whilst undertaking the programme; and the ways in which agency, culture and structural constraints interacted in their participation and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some related to the role of E2E tutor and the work of Connexions PAs, and are discussed in Thompson (2010) and Russell, Simmons and Thompson (2010), respectively. In this paper, three broad themes concerning learners are explored: how they came to access E2E; their learning experiences whilst undertaking the programme; and the ways in which agency, culture and structural constraints interacted in their participation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, those deemed not to be making progress, or to be otherwise unsuitable for E2E, could be referred back to Connexions. Furthermore, our research found that in some cases, funding constraints and demand for places resulted in learners being required to leave the programme before they were fully ready (see Russell, Simmons, and Thompson 2010).…”
Section: E2e Learners and Access Tomentioning
confidence: 99%
“…There is also some research on advice and guidance for marginalised young people (Russell et al, 2010), and on employability programmes (Russell et al, 2011;Higgins, 2013;Smyth et al, 2013). Numerous business surveys highlight claims by employers of 'skills gaps', particularly 'soft skills' (Sissons & Jones, 2012, p. 21).…”
Section: Introductionmentioning
confidence: 99%
“…It is also notable that Connexions experienced challenges relating to both funding constraints (Russell, Simmons, and Thompson 2010) and the organisations' wide and shifting remit (Sheehy, Kumrai, and Woodhead 2011). Not least of these challenges was the transfer of responsibility for Connexions to Local Authorities outlined in the Youth Matters green paper and effected by 2008 to create a range of different delivery models across England (Watts and McGowan 2007).…”
Section: Neet Under the Last Labour Governmentmentioning
confidence: 99%